Influence of Shoot Cutting on Growth Descriptors and Biomass Yield of Dhaincha Plant (Journal of the Bangladesh Agricultural University, 2024)
Dhaincha (Sesbania spp.), a multipurpose quick-growing, succulent and easily decomposable herb, is an ideal green manure crop. Shoot cutting at a specific height or time might be one of the options for the biomass yield maximization. To evaluate the influence of shoot cutting on morphological and reproductive descriptors and biomass yield, an experiment was carried out with eight dhaincha accessions representing three Sesbania species, viz. S. bispinosa (Acc #5, 71, 77 and 103), S. cannabina (Acc #25, 28) and S. sesban (Acc #82 and 85), and three times of shoot cutting at 8, 9 and 10 weeks after sowing (WAS) keeping plant height 25 cm above the ground level. The experiment was laid out on a randomized complete block design with three replications. The results revealed that cutting time had a significant effect on biomass yield and other descriptors; and showed a decreasing trend with delay in cutting treatments. The biomass yield ascended to 37 per cent in cutting at 8 WAS than the uncut control plants. Among the species, S. bispinosa responded positively (increase in biomass yield and other descriptors) to the cutting treatments, however, S.cannabina and S. sesban responded negatively. Accession #77 produced the highest fresh weight (340 g 10–1 plants) and biomass yield (190 g 10–1 plants) in cutting at 8 WAS and accession #82 and #85 produced the lowest biomass yield in cutting at 10 WAS. The optimum cutting time would be 8 WAS to produce higher biomass of dhaincha. Among the accessions, #77 may be recommended to cultivate as a green manure crop due to its higher biomass yield.J Bangladesh Agril Univ 18(3): 585–592, 2020https://doi.org/10.5455/JBAU.116218